2015
DOI: 10.3892/ol.2015.3032
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanisms of blocking the hedgehog signaling pathway in human gastric cancer cells

Abstract: Abstract. Excessive activation of the hedgehog (Hh) signaling pathway is important in a variety of human cancer cell types, including gastric cancer. However, the underlying mechanisms of the Hh signaling pathway in inducing gastric tumorigenesis and its downstream target genes are largely unknown. In the present study, the inhibitory effect of cyclopamine on the Hh signaling pathway was investigated in the human gastric cancer AGS cell line. It was identified that cyclopamine treatment inhibited the prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In contrast, the Hh signalling in the hepatocytes from the C57BL/6N mice was blocked for only 24 h after preparation in the 2D cell culture; therefore, they were exposed to impaired Hh signalling for a much shorter time and were not exposed to systemic effects. Unfortunately, we could not detect significant downregulation of Gli1 and Ptch1 in primary hepatocytes treated with cyclopamine for 24 h as it is known for numerous other cell types [35,36]. Several reasons for this apparent discrepancy are discussed below.…”
Section: Hh/mtor Crosstalk In Hepatocytesmentioning
confidence: 69%
“…In contrast, the Hh signalling in the hepatocytes from the C57BL/6N mice was blocked for only 24 h after preparation in the 2D cell culture; therefore, they were exposed to impaired Hh signalling for a much shorter time and were not exposed to systemic effects. Unfortunately, we could not detect significant downregulation of Gli1 and Ptch1 in primary hepatocytes treated with cyclopamine for 24 h as it is known for numerous other cell types [35,36]. Several reasons for this apparent discrepancy are discussed below.…”
Section: Hh/mtor Crosstalk In Hepatocytesmentioning
confidence: 69%
“…Previous studies have shown that HH signaling plays a pivotal role in regulating cell migration [46]. There, we examined the potential effect of HHIP over-expression on GC cell migration with the “Transwell” assay.…”
Section: Resultsmentioning
confidence: 99%
“…More inhibitors have been developed to target SMO than SHH or GLI. Cyclopamine, the first reported SMO inhibitor, exhibits inhibitory activity in vitro gastrointestinal tumors models 33 , 49 , 50 . Saridegib (IPI-926), a semisynthetic analog of cyclopamine, with improved chemical stability and biological activity, has entered a phase I clinical trial for the treatment of gastric cancer 144 .…”
Section: Hh Signaling As a Potential Clinical Prognostic And Therapeumentioning
confidence: 99%
“…HH inhibitors that have been effective in treating gastrointestinal tumors include isoflavone 30 , 31 , imiquimod 32 and 5E1 33 . SMO inhibitors that have been effective in treating gastrointestinal tumors include vismodegib 29 , 34 , 35 , vitamin D3 36 , 37 , 38 , BMS-833923 39 , TAK-441 40 , saridegib 41 , itraconazole 42 , 43 , 44 , miR-218 45 , 46 , 47 , MS-0022 48 , cyclopamine 33 , 49 , 50 and KAAD-cyclopamine 51 . GLI inhibitors that have been effective in treating gastrointestinal tumors include curcumin 52 , 53 , 54 , resveratrol 55 , 56 , epigallocatechin-3-gallatel 57 , 58 , arsenic trioxide 59 , 60 , 61 , GANT 61 62 , 63 , 64 , zerumbone 65 , sodium arsenite 66 and AY9944 67 .…”
Section: Introductionmentioning
confidence: 99%